Field evaluation of a photonics‐based radar system in a maritime environment compared to a reference commercial sensor. Issue 8 (1st October 2015) - Laghezza, Francesco; Scotti, Filippo; Serafino, Giovanni; Banchi, Luca; Malaspina, Vincenzo; Ghelfi, Paolo; Bogoni, Antonella
Abstract : This study shows the experimental validation of the first photonics‐based radar system demonstrator in a real maritime environment. The radar system demonstrator exploits photonic technologies for both the generation and the detection of the RF radar signals, and it has been previously proved allowing increased performance and unprecedented potential flexibility. Here, the photonics‐based radar is compared with a commercial system for maritime applications provided by 'GEM elettronica'. The analysis has checked the performance of the photonics‐based system in terms of transmitted signal integrity and receiver pre‐ and post‐detection capability, by means of ad‐hoc laboratory tests and an on‐field direct comparison, run into the operative scenario of the port of San Benedetto del Tronto (Italy), by observing non‐cooperative targets. The reported results show that the photonics‐based radar system, although at a demonstrator stage, proves comparable performance with the commercial radar used as reference. Beyond the actual implementation of the proposed system, the outcomes of this comparison confirm that the photonics‐based approach can lead new advances in radar architecture, by the development of a completely frequency and waveform agility, application‐transparent photonic transceiver.